A name for the nurse-frog (Allobates, Aromobatidae) of Floresta Nacional de Carajás, Eastern Brazilian Amazonia - Simões, Pedro Ivo; Rojas, Diana; Lima, Albertina P. (Zootaxa, 2019)
We describe a new species of nurse-frog (Aromobatidae, Allobates) from Floresta Nacional de Carajás, southeastern Brazilian Amazonia. Allobates carajas sp. nov. is distinguished from similar congeneric species by the combination of the following characters: body-size range (snout-to-vent length 16.5–19.1 mm), dorsal color pattern with a dark brown hourglass-shaped mark, by the absence of a pale dorsolateral stripe and presence of a pale ventrolateral stripe, absence of a pale paracloacal mark, by overall bright yellow ventral colors of live male and female specimens, and by the posterior labium of tadpoles, with a single row of pyramidal papillae medially. The advertisement call of the new species is highly variable, with four possible temporal arrangements of notes (continuous emission of notes separated by regular silent intervals, continuous emission of notes separated by irregular silent intervals, emission of discrete note trills, and sporadic emission of single notes). Duration of notes range between 0.020–0.060 s, and the dominant frequency of notes range from 4.75 to 5.38 kHz. The new species is currently known only from forested habitats within Floresta Nacional de Carajás.